Nanotechnology-Based Drug Delivery in Cancer and Neurological Disorders - Shah, Priya; Prajapati, Umang; Patel, Henil; Kumar, Ashok (Journal of Pharmacy Practice and Community Medicine, 2026)
Nanotechnology has revolutionised drug delivery by enabling the design of nanoscale carriers (1-100 nm) with tunable physicochemical properties that allow precise targeting, improved bioavailability, and controlled release of therapeutic agents. Nanoparticles such as liposomes, polymeric and metallic nanocarriers, dendrimers, and lipid-polymer hybrids have significantly enhanced cancer and Central Nervous System (CNS) therapies by overcoming biological barriers like the tumour microenvironment and the Blood-Brain Barrier (BBB). In oncology, passive and active targeting approaches exploit tumour vasculature permeability and receptor overexpression to achieve localised drug accumulation, while in neuropharmacology, nanocarriers facilitate transcytosis-based transport across the BBB for diseases such as Alzheimer’s and glioblastoma. Emerging smart and stimuli-responsive systems further enable site-selective drug release in response to pH, enzyme activity, and redox potential, minimising systemic toxicity. The integration of AI (Artificial Intelligence) into nanocarrier design is accelerating the optimisation of nanoparticle properties and therapeutic precision. Despite these advances, challenges in clinical translation, such as nanoparticle toxicity, manufacturing reproducibility, and regulatory approval, persist. Looking forward, interdisciplinary innovations integrating AI, genomics, and personalised nanomedicine promise a new era of precision drug delivery for oncology and neurological disorders, paving the way toward safer, more effective, and patient-tailored therapeutics.
Keywords: Blood-brain barrier; Cancer therapy; Nanomedicine; Nanotechnology; Targeted; delivery